A novel RNA‐based adjuvant combines strong immunostimulatory capacities with a favorable safety profile. Issue 2 (8th January 2015) - Heidenreich, Regina; Jasny, Edith; Kowalczyk, Aleksandra; Lutz, Johannes; Probst, Jochen; Baumhof, Patrick; Scheel, Birgit; Voss, Söhnke; Kallen, Karl‐Josef; Fotin‐Mleczek, Mariola
<x xml:space="preserve">Abstract</x> Protein‐ and peptide‐based tumor vaccines depend on strong adjuvants to induce potent immune responses. Here, we demonstrated that a recently developed novel adjuvant based on a non‐coding, long‐chain RNA molecule, termed RNAdjuvant®, profoundly increased immunogenicity of both antigen formats. RNAdjuvant® induced balanced, long‐lasting immune responses that resulted in a strong anti‐tumor activity. A direct comparison to Poly(I:C) showed superior efficacy of our adjuvant to enhance antigen‐specific multifunctional CD8+ T‐cell responses and mediate anti‐tumor responses induced by peptide derived from HPV‐16 E7 protein in the syngeneic TC‐1 tumor, a murine model of human HPV‐induced cervical cancer. Moreover, the adjuvant was able to induce functional memory responses that mediated complete tumor remission. Despite its remarkable immunostimulatory activity, our RNA‐based adjuvant exhibited an excellent pre‐clinical safety profile. It acted only locally at the injection site where it elicited a transient but strong up‐regulation of pro‐inflammatory and anti‐viral cytokines as well as cytoplasmic RNA sensors without systemic cytokine release. This was followed by the activation of immune cells in the draining lymph nodes. Our data indicate that our RNA‐based adjuvant is a safe and potent immunostimulator that may profoundly improve the efficacy of a variety of cancer vaccines.